PARITAS DAN UMUR IBU HAMIL DENGAN KEJADIAN HIPERTENSI DALAM KEHAMILAN - Henny Juaria (Akademi Kebidanan Griya Husada Surabaya, 2017)
Complications of hypertension in pregnancy are the third largest in the main causes of maternal death. Based on the results of a secondary data survey at Sawahan Surabaya Health Center in 2015 which experienced hypertension in pregnancy as much as 35.48%, and an increase from 2014-2015 of 7.45%, while the tolerance rate for hypertension according to the East Java Health Office was 5% . So there is still a high incidence of hypertension in pregnant women at Sawahan Health Center Surabaya, so this problem needs to be carried out research that aims to determine the relationship between parity and age with the incidence of hypertension in pregnancy. Method: This research method uses analytical research with a cross sectional approach with a population of 78 people and a sample of 65 people, sampling by simple random sampling. The results of the study were made frequency tables, cross tabulated and analyzed by chi-square test with the provisions of ? = 0.05 with tabel2 tables = 3.84 Results: From the results of the study showed mothers who had multiparous parity who had hypertension were 38 people (58.86% ) and at the age of the majority of mothers aged> 35 years as many as 40 people (61.54%). After the chi-square test, it was found that itung2 count> ?2 table which means rejecting H0. Discussion: There is a relationship between parity and maternal age with the incidence of hypertension in pregnancy. An effort that can be done is to give IEC about nutrition improvement for pregnant women by consuming foods that are nutritiously balanced and without having to be expensive, as well as eating foods that are low in salt. With foods that are low in salt can prevent edema, make home visits to pregnant women so that they can prevent the occurrence of hypertension in pregnancy.